PERAN LINGKUNGAN, PERTIMBANGAN PASAR KERJA DAN PERSEPSI MAHASISWA PENGARUHNYA TERHADAP KEPUTUSAN MAHASISWA BERKARIR DI BIDANG PERPAJAKAN - I Nyoman Putra Yasa; Ida Ayu Gede Danika Esa Pradnyani; Anantawikrama Tungga Atmadja (Faculty of Economics and Business, Universitas Warmadewa, 2019)
This research was aimed to determine the effect of the role of environment, job market consideration, and student perception of career choices in the field of taxation. The type of research conducted was quantitative research. The population of this research was undergraduate students of accounting department of Ganesha University of Education. The method used to determine the sample was the purposive sampling method. The data were collected by distributing questionnaires to 375 respondents. The data analysis technique used was multiple regression analysis. The results of this research indicated that the role of family environment, campus environment, job market consideration and student perception have a positive impact either individually or together influenced the choice of career in the field of taxation.